HPTLC fingerprint profile analysis of cocoa proanthocyanidins depending on origin and genotype. (30th November 2018) - Pedan, Vasilisa; Weber, Carlo; Do, Tiên; Fischer, Norbert; Reich, Eike; Rohn, Sascha
Highlights: A fast screening tool for the quantification of cocoa polyphenols was developed. Compounds were monitored for 31 cocoa bean samples from various origins. HPTLC fingerprints can be used for quality control in chocolate manufacturing. Anthocyanins as key indicators for fermentation state were described. Abstract: Cocoa beans are rich in bioactive phytochemicals such as alkaloids, anthocyanins, as well as monomeric and oligomeric flavan-3-ols. A high performance thin layer chromatography (HPTLC) method was developed for a fast analysis of a fingerprint of bioactive compounds present in cocoa beans depending on genotype and origin. Evaluation was performed using HPTLC followed by densitometry. The best separation for a fingerprint consisting of eight phenolic compounds as markers was achieved on silica gel 60 F254 HPTLC plates with a solvent mixture of ethyl formate, formic acid, water, toluene 30/4/3/1.5 (v/v/v/v). Staining with Fast Blue Salt B enabled visualization and quantitative evaluation. Compounds of interest were confirmed by eluting zones using a TLC-MS interface. LODs were ≤ 100 ng/zone for all compounds. The fingerprints obtained are useful for quality control of cocoa beans allowing their differentiation according to cocoa or chocolate sorts, varieties, and origins.